The Political and Moral Economies of Neoliberalism: Mises and Hayek - Rodrigues, João (2013)
This article compares the political and moral economies of Ludwig von Mises and Friedrich Hayek. It argues that some of the relatively less scrutinised intellectual divergences are located in their views on the roles of the state within a market society. Convergences will also be identified, particularly in the field of moral economy, where despite their different positions on rationalism and utilitarianism, one can find a fundamental agreement on the positive causal effects of certain economic institutions on values. This is accompanied by a sceptical view on the future of market society related to the ongoing strength of institutions fostering ideologies inimical to markets, which is one of the factors explaining the importance both gave to the battle of ideas and to the corresponding effort to deliberately shape public opinion.